Filsafat Ekologi dan Pengetahuan Lokal untuk Mencapai Konservasi Keanekaragaman Hayati yang Holistik: Filsafat Ekologi dan Pengetahuan Lokal untuk Mencapai Konservasi Keanekaragaman Hayati yang Holistik - Sulistiyowati, Eka (Jurnal Filsafat Indonesia, 2024)
This study examines the approach of two main conservation movements, namely ecological conservation and social conservation. The purpose of this study is to reflect on the philosophical basis of ontology, epistemology, and axiology to achieve holistic conservation work. The method used is a reflective qualitative method using narrative literature review. This study found that to end the debate on ecological and social conservation is to integrate components of local knowledge based on local philosophy that are rooted in local knowledge and are holistic.